2018
DOI: 10.1190/geo2017-0682.1
|View full text |Cite
|
Sign up to set email alerts
|

Full-intensity waveform inversion

Abstract: Many full-waveform inversion schemes are based on the iterative perturbation theory to fit the observed waveforms. When the observed waveforms lack low frequencies, those schemes may encounter convergence problems due to cycle skipping when the initial velocity model is far from the true model. To mitigate this difficulty, we have developed a new objective function that fits the seismic-waveform intensity, so the dependence of the starting model can be reduced. The waveform intensity is proportional to the squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…It is recognized that FWI is sensitive to inaccurate starting models and the lack of low‐frequency data due to the cycle‐skipping problem. To mitigate the problem of cycle‐skipping, substantial efforts have been made to establish a reliable starting model for FWI, such as emphasizing low‐wavenumber updates (Alkhalifah, ; Kazei & Alkhalifah, ; Wu & Alkhalifah, ; Xie, ; Yao et al, ), modulating low‐frequency components (Bharadwaj et al, ; Bozdağ et al, ; Chi et al, ; Liu et al, ; Shin & Cha, ), and building more effective objective functions (Leeuwen & Mulder, ; Yi et al, ; Zhang et al, ; Zhang & Alkhalifah, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that FWI is sensitive to inaccurate starting models and the lack of low‐frequency data due to the cycle‐skipping problem. To mitigate the problem of cycle‐skipping, substantial efforts have been made to establish a reliable starting model for FWI, such as emphasizing low‐wavenumber updates (Alkhalifah, ; Kazei & Alkhalifah, ; Wu & Alkhalifah, ; Xie, ; Yao et al, ), modulating low‐frequency components (Bharadwaj et al, ; Bozdağ et al, ; Chi et al, ; Liu et al, ; Shin & Cha, ), and building more effective objective functions (Leeuwen & Mulder, ; Yi et al, ; Zhang et al, ; Zhang & Alkhalifah, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [12] proposed a waveform mode decomposition method to recover the low frequency components of the observed data. Liu et al [13] fitted the intensity of the observed and synthetic data, and found that sufficient low-frequencies in the intensity data can help FWI avoid cycle skipping. Sun and Demanet [14] used high frequency signals as training set and used deep learning based on the convolutional neural network to extrapolate low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lots of efforts have been made to find better objective functions that are immune from cycle skipping (Liu et al, 2018;Zhang et al, 2018a;Wu et al, 2019;Yi et al, 2019). The conventional wiggle-to-wiggle subtraction based measurement fails FWI when the predicted and observed data exceed the half-cycle limit (Virieux and Operto, 2009).…”
Section: Introductionmentioning
confidence: 99%